ANALISIS TINGKAT PELAYANAN AIR BERSIH DAN PENINGKATAN OPERASIONAL POMPA BOSTER PADA JARINGAN PIPA DISTRIBUSI JALAN A.W. SYAHRANI KOTA SAMARINDA - SYAM, ANWAR (KURVA S JURNAL MAHASISWA, 2014)
Water is a primary need for daily human life, therefore the provision of clean water for rural and urban population is absolutely necessary. Regional Water Company (PDAM) Samarinda City as well as in particular Water Treatment Plant (IPA)Network Distribution Pipeline Road AW Syahrani in serving residents who live in North Samarinda and the surrounding region has a very important role in providing clean water as a basic necessity of life that meets the requirements, both in terms of aspects of quality, quantity and continuity. Distribution of water in the region of North Samarinda impaired due to malfunction of the booster pump in Jalan A.Wahab Syahrani optimally, despite being pursued distribution in rotation but until now did not go well.So to be able to improve service water needs Distribution Pipeline Road AW Syahrani mentioned above and in order to maintain necessary strategic steps and efficient and a good management system and operational improvements pump booster, including for the needs of 10 (ten) years into the future, so that the needs of the community and the public as well as the smooth development can be met and there is no occur sharing.From the analysis and calculations as well as the discussion on this research, the projected service levels IPA Distribution Pipeline Road AW Syahrani the next ten years (2015-2024) for conditions of service of its growth rate of 1.30% / year, water production growth rate 8.81% / year , water distribution growth rate of 8.31% / year, water sales revenue growth rate of 1.70% / year, operating cost growth rate of 1.43% / year. In Efforts to increase revenue IPA Distribution Pipeline Road AW Syahrani, by used Maintenance booster pump system (Routine Maintenance, Predictive Maintenance, Preventive Maintenance) and increasing the capacity of booster pump